Attribute Agenda Building in An Environmental Crisis: News Coverage of MV X-Press Pearl Ship Incident in Sri Lanka - P. C. P. Kumara; Hewage , Galagedarage Thushari Madhubhashini (UIR Press, 2024)
This study investigated the building of the attribute agenda of an environmental crisis, taking the MV X-Press Pearl shipwreck incident as a case study. English weekend newspapers for a year since the incident were used for a content analysis to identify the information subsidies and their respective attribute agendas. An analysis framework was developed based on information subsidies and their respective attribute agendas. Results indicated that the governmental bodies unrelated to the environment were the most frequently cited sources, followed by experts and local non-governmental organizations/ industries. Conversely, the public was the least cited information source. Environmental damage was the most frequently emphasized attribute, followed by law and agreements and prevention. However, policy was the least reported attribute. Considering the correlation between information sources and attributes, the Marine Environmental Protection Authority highlighted the mitigation agenda, while non environmental related governmental bodies emphasized prevention agenda. Policymakers focused on getting compensation, while governmental bodies emphasized law and agreements and Experts prioritized on environmental damage. The evidence for attribute agenda building was found further strengthening the agenda building hypothesis and information subsidies had their own attributes highlighted in media reports. The study delves into the practical implications of agenda building, which can influence media outlets. It suggests strategic communication planning, aligning coverage with objectives, and collaborating with environmental advocacy groups. This understanding informs decision-making, promotes balanced coverage, and enhances public engagement. It is important to additionally take into account the process used to establish the agenda in future research.